On-chip guiding of higher-order orbital angular momentum modes - Lee, In Joon; Kim, Sangin (Photonics, 2019)
Higher-order orbital angular momentum (OAM) mode guiding in a waveguide which is suitable for on-chip integration has been investigated. Based on the relation between the Laguerre-Gaussian mode and the Hermite-Gaussian mode, it has been shown that two degenerate guided modes of ϕ/2l-rotation symmetry can support the l-th order OAM mode. In order to mimic the rotational symmetry, we have proposed the waveguide structure of a cross-shaped core and designed a waveguide that can support OAM modes of ±1 and ±2 topological charges simultaneously at a wavelength of 1550 nm. Purity of the OAM modes guided in the designed waveguide has been assessed by numerically calculating their topological charges from the field distribution, which were close to the theoretical values. We also investigated the guiding of OAM modes of ±3 and ±4 topological charges in our proposed waveguide structure, which revealed the possibility of the separate guiding of those OAM modes with relatively lower purity.
Keywords: Higher order orbital angular momentum modes; On-chip orbital angular momentum mode; Orbital angular momentum; Silicon waveguide